2011
DOI: 10.1027/0227-5910/a000062
|View full text |Cite
|
Sign up to set email alerts
|

The Therapist’s Reaction to a Patient’s Suicide

Abstract: Our data suggest that identifying the severely distressed subgroup could be done using a visual analog scale for overall distress. As a consequence, more specific and intensified help could be provided to these professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Smith and Jones did. Surveys of providers who experienced a suicide in their practice found that funeral attendance was relatively un-common, with rates ranging from 2% to 14% of providers (21, 28, 31, 44). The literature does suggest, however, that funeral attendance after a patient suicide can help families and providers mourn and work through their grief after suicide (24, 31, 45, 46).…”
Section: Interacting With Familiesmentioning
confidence: 99%
“…Smith and Jones did. Surveys of providers who experienced a suicide in their practice found that funeral attendance was relatively un-common, with rates ranging from 2% to 14% of providers (21, 28, 31, 44). The literature does suggest, however, that funeral attendance after a patient suicide can help families and providers mourn and work through their grief after suicide (24, 31, 45, 46).…”
Section: Interacting With Familiesmentioning
confidence: 99%
“…patient's level of suicide risk, extent of responsibility for risk management, required process following a death, likely impact, support available). As highlighted elsewhere, we need to better prepare practitioners for such losses (Bowers et al, 2006 ; Chemtob et al, 1988 ; Gibbons et al, 2019 ; Hendin et al, 2000 ; Jacobson et al, 2004 ; Sherba et al, 2018 ; Wang et al, 2016 ; Wurst et al, 2011 ). This lack of preparation could combine with personal characteristics (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Although data are limited and ranges across mental health settings, one study of exposure among a national sample of counselors ( N = 376) found that 24% experienced the death of a client by suicide (McAdams & Foster, 2000). Other studies found that practitioners working in inpatient psychiatric settings experienced higher rates of exposure (i.e., 55%–69%; Takahashi et al, 2011; Wurst et al, 2011). However, examination of the frequency of school counselors’ exposure to a student’s death by suicide is needed given the prevalence of youth suicide and the critical role that school counselors play in youth suicide prevention and crisis response (ASCA, 2018; Fineran, 2012).…”
Section: Suicide Exposure Research Among Helping Professionalsmentioning
confidence: 96%
“…Client suicide can have serious consequences on mental health professionals’ emotional well-being and professional work. Personal reactions to clients’ death by suicide include sadness, depression, guilt, anger, shame, personal distress, shock, emotional numbing, and social withdrawal (Finlayson & Simmonds, 2016; McAdams & Foster, 2000; Sanders et al, 2005; Sherba et al, 2019; Wurst et al, 2011). Further, some professionals experiencing clients’ death by suicide have trauma-related symptoms including traumatic stress, intrusive thoughts (e.g., dreams or thoughts about the suicide), avoidance (i.e., efforts to avoid feelings or situations related to the suicide), and hyperarousal (e.g., being “on guard”; Castelli Dransart et al, 2014; McAdams & Foster, 2000; Sanders et al, 2005; Takahashi et al, 2011).…”
Section: Suicide Exposure Research Among Helping Professionalsmentioning
confidence: 99%